Desenvolvimento de filmes hierárquicos à base de celulose bacteriana e zeólita (Ca, Cu, Zn)A para liberação controlada de óxido nítrico - Alexandre, Natália Porto (2020)
The search for efficient materials for the release of NO has been growing in recent years, allowing the study of microporous materials, among which are highlighted as zeolites, which reproduce well-organized pore systems and increase the adsorption capacity. However, its powder form restricts NO access to active centers, limiting the amount of gas that can be adsorbed. As an alternative, in this work, the hierarchy of type A zeolite is proposed by means of dispersion in a polymeric matrix, bacterial cellulose (CB), for controlled release of nitric oxide, with a view to antimicrobial applications. In this study, zeolite A films were developed, in Ca2+, Cu2+ and Zn2+ forms, in bacterial cellulose matrices, in the proportions of 12.5% and 25% (m / m), for testing in storage and controlled release from NO. The materials obtained were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), X-ray scattering spectroscopy (EDS), infrared absorption spectroscopy (FTIR), spectroscopy of photoelectrons excited by X-rays (XPS) and thermogravimetric analysis (TG). Through XRD techniques, it was possible to identify different intensities in each zeolite exchanged, due to the fact that cations may have different affinities in the occupation of the sites. SEM analyzes showed zeolitic crystals interlaced by CB fibers with agglomeration of zeolite crystals in 25% (m / m) films, which makes it difficult to adsorb nitric oxide and make the films less efficient compared to 12% (m / m). The XPS measurements showed changes in the binding energies, which may indicate the interaction between the zeolite and cellulose surfaces, which makes it possible to verify the formation of the hierarchical structure material. Therefore, the hierarchy resulting from the dispersion of the zeolitic crystals over the CB fibers, as well as the ion exchange process, influenced the capacity of retention / release of NO by the zeolite, in which it was possible to obtain superior performance than its isolated forms, reaching 0.6 mmol NO / g of zeolite.